SEJARAH SINGKAT RADIO, FORMAT, PERANGKAT SIARAN, REVOLUSI SERTA KEUNGGULAN DAN KELEMAHANNYA - Winda Kustiawan; Ja’far, Ja’far; Amran Sahputra Tanjung; Ali Akbar Siregar; Azbar Rifa’i; Anggi Martuah Purba (Lembaga Pengembangan Kinerja Dosen, 2022)
The emergence of radio as a mass media facilitates access to information for its users. Radio has advantages that are not owned by other mass media. Radio has a wide enough reach so that information conveyed via radio can be directed to all corners of the world, especially with its current development supported by the use of the Internet which makes it easier for users to access online radio. The history of radio was first developed by Guglielmo Marconi, an expert from Italy. Until now there are many types of radio and various tools used in radio broadcasts in broadcast studios. This article discusses a brief history, formats, broadcast equipment, revolutions or developments, as well as the advantages and disadvantages of radio.